Virtual reality in the teaching of fle in a brazilian public school - Nobrega, Felipe Augusto [UNESP]; Rozenfeld, Cibele Cecílio de Faria [UNESP] (MDPI, 2019)
Considering the emergence of digital information and communication technologies in the contemporary educational context, this work aims to explore the possibilities offered by Virtual Reality (VR) headsets in the school environment, and also to verify how they can contribute to foreign language teaching and learning. The motivation of this work is a result of a pedagogical practice experience carried out by the researcher during French classes in a Brazilian foreign language teaching project in public schools. This pedagogical practice later became the subject of their master’s research, which is currently being conducted in the same educational context in two French language classes. The main objective consists of verifying to what extent VR can contribute to foreign language teaching/learning, focusing on the four linguistic competences and motivation. The methodology of this work has a qualitative nature with some quantitative results, and is characterized as Action Research, as the researcher participated in the activities. These activities consisted of using Google Cardboard, a VR headset, to present interactive 360◦ videos and tours of real places. The preliminary results show that activities with VR can promote a high level of motivation and engagement, also contributing to the development of the four linguistic competences.
Keywords: Français Langue Étrangère; Google Cardboard; Language learning; Virtual Reality